EFEKTIFITAS KOMPRES HANGAT DAN AKUPRESUR TERHADAP NYERI PUNGGUNG BAGIAN BAWAH PADA IBU HAMIL TRIMESTER III LITERATURE REVIEW - Prabandani, Kirana Dwi; Leny Wulandari, Rr. Catur; Zahriah, Atika (Politeknik Kesehatan Kemenkes Bengkulu, 2021)
During pregnancy many physical and psychological changes occur in women, one of which is the enlargement of the uterus which can cause back pain. Back pain is an inconvenience for pregnant women, especially in the third trimester. Untreated back pain can interfere with daily activities. Pregnant women can reduce back pain by using non-pharmacological therapies such as warm compresses and acupressure. The purpose of the literature review is to determine the effectiveness of warm compresses and acupressure on lower back pain in third trimester pregnant women. The method used is a literature review on a health journal database, namely Google Scholar, obtained 59 articles, 27 articles in Pubmed, 5 articles in The Lancet, 28 articles in Springer and in Elsevier 1 article published in the last 10 (ten) years. The results of the literature study show that warm compresses and acupressure are effective methods to reduce back pain complaints in third trimester pregnant women. Warm compresses and acupressure are both effective in reducing back pain scale, but warm compresses are easier to use than acupressure which must be done and accompanied by someone who is trained.